Investigation of radioactivity concentration of 137Cs, 90Sr and 129I radioisotopes in thyroid samples - Kayakoku, Halime; Dogru, Mahmut; Kucukonder, Adnan (Elsevier Sci Ltd, 2020)
In this study, the gross alpha and beta activities and Cs-137, Sr-90 and I-129 radionuclide concentrations in the feeds and thyroid samples obtained from a certain number of sheep, which were fed by Firat University (Elazig) Faculty of Veterinary Medicine with varying amounts of fresh lucerne, fodder, silage, straw and concentrate feed were determined. The Cs-137, Sr-90 and I-129 radionuclide transfer coefficients were also determined. Sr-90 and I-129 are beta-emitting radionuclides. Sheep with high Sr-90 and I-129 radionuclide concentrations also have high gross beta radioactivity levels. When an intragroup comparison is performed, the radionuclide concentration in a sheep fed with maximum feed is at the highest level and vice versa. Moreover, the Cs-137, Sr-90 and I-129 radionuclide transfer coefficients (F-f) for the thyroid samples obtained from the sheep vary between 0.4 x 10(-1) - 8.1 x 10(-1) d kg(-1), 0.4 x 10(-2) - 6.1 x 10(-1) d kg(-1) and 0.4 x 10(-1) - 7.3 x 10(-1) d kg(-1), respectively, and are higher than the expected Ff values and the results obtained in similar studies. The Ff values calculated for the thyroid samples of the straw and fodder group are lower than the F-f values calculated for the thyroid samples of the silage and fresh lucerne group. The radionuclide concentrations for I-129 were found to be higher than Sr-90's in the thyroid samples.
Keywords: Radioactivity; (117)cs; Sr-90; I-129; Transfer coefficient